AB0558 Juvenile-Onset Behçet's Disease: Clinical and Genetic Features Compared with Adult Onset-Disease. (15th July 2016) - Ben Salem, T.; Naceur, I.; Tougorti, M.; Ben Ghorbel, I.; Lamloum, M.; Houman, M.H.
Abstract : Background: Behçet's disease (BD) is are in children. Objectives: The aim of this study was to describe clinical spectrum of BD in childhood in comparison to adult onset-disease. Methods: We conducted a retrospective study over 10 years including 430 patients with the diagnosis of BD according to the criteria of the International Study Group. The patients were placed into two groups based on the age of the disease onset: group1: juvenile-onset (≤16 years) and group 2: adult-onset disease (age >16 years). Clinical, genetic and therapeutic characteristics of juvenile patients were analyzed and compared with adult patients Results: There were 38 cases with juvenile onset disease (24 males, 14 females; gender ratio M/F: 1.7). A family history of BD was found in 3 patients. The mean age of the disease onset in this group was 12.8 years ±2.9 and the average age at BD diagnosis was 21.55 years ±7.47. Genital ulcers were observed in 71% of cases. Skin lesions were found in 76.3% of patients and positive pathergy test in 70.4%. Nineteen patients (50% of cases) had ocular involvement (uveitis: 18 cases, retinal vasculitis: 10 patients) which was complicated of blindness in 2 cases. Neurological involvement was observed in 8 patients (21% of cases). Eight patients presented vascular lesion (superficial venous thrombosis: 5 cases, deep venous thrombosis: 3 cases), no cases of arterial involvement was noted. HLA B51 was found in 62.5% of cases. Comparative study of the 2 groups showed that children with BD had significantly less deep venous thrombosis and more superficial venous thrombosis. The ocular involvement was relatively less severe in children (blindness: 15.4% vs 32.5%). Treatment was based in colchicine, corticosteroids (73.7%) and immunosuppressant agents. Cyclophosphamides were more used in adults (45.6% vs 26.3%; p=0.02) and azathioprine in children (46% vs 33%; p=0.08). Conclusions: Behçet's disease in children is characterized in our series by the frequency of superficial venous thrombosis and seems to run a less severe course (less DVT and blindness, no arterial involvement and less use of cyclophosphamide). An appropriate and early treatment would prevent the occurrence of serious visceral complications in these patients. Disclosure of Interest: None declared